Role of postoperative adjuvant therapy in resected invasive intraductal papillary mucinous neoplasm of the pancreas: A multicenter external validation. (14th June 2021) - Choi, Munseok; Chong, Jae Uk; Hwang, Ho Kyoung; Seo, Hyung‐Il; Yang, Kwangho; Ryu, Je Ho; Roh, Younghoon; Kim, Dong Hyun; Lee, Jin Ho; Lee, Woo Jung; Choi, Sung Hoon; Kang, Chang Moo
Abstract: Background: Adjuvant therapy is beneficial in prolonging survival in patients with pancreatic ductal adenocarcinoma (PDAC). However, no clear guidelines are available on the oncologic effect of adjuvant therapy in resected invasive intraductal papillary mucinous neoplasms (inv‐IPMN). Methods: In total, 551 patients with PDAC and 67 patients with inv‐IPMN of the pancreas were reviewed. For external validation, 46 patients with inv‐IPMN from six other Korean institutions were enrolled. Propensity score‐matched analysis and stage‐matched survival analysis were conducted. Results: The mean follow‐up durations in the inv‐IPMN and PDAC groups were 43.36 months (SD, 42.34 months) and 43.35 months (SD, 35.62 months), respectively. The 5‐year overall survival (OS) was significantly better in the resected inv‐IPMN group than in the PDAC group in the overall stage‐matched analysis ( P  < .001). In the inv‐IPMN cohort, OS was better in the surgery alone group ( P  = .042). In subgroup analysis, no significant survival difference was found between the adjuvant therapy and surgery alone groups according to the stage (stage I; P  = .285, stage II or III; P  = .077). Multicenter external validation did not show a better OS in the adjuvant therapy group ( P  = .531). On multivariable analysis, only perineural invasion (PNI) was identified as an adverse prognostic factor in resected inv‐IPMN (HR 4.844; 95% CI 1.696‐13.838, P  = .003). Conclusions: inv‐IPMN has a more indolent course than PDAC. Current strategy of adjuvant therapy may not improve the OS in patients with resected inv‐IPMN. Further investigations on the potential role of adjuvant therapy in inv‐IPMN are mandatory. Abstract : Highlight No clear guidelines are available on the oncologic effect of adjuvant therapy in invasive intraductal papillary mucinous neoplasm of the pancreas. Choi and colleagues found no evident effect of adjuvant therapy in patients who underwent resection. Further prospective studies based on large populations are warranted to validate the present observations.